THE ROLE OF COMPUTER EDUCATIONAL GAMES IN THE INNOVATIVE EDUCATION SYSTEM (Western European Journal of Modern Experiments and Scientific Methods, 2024)
This article examines the use of computer games in the educational process, one of the most powerful socio-psychological factors influencing the spirituality of youth. The results of a social survey and experiments are presented. Suggestions are given on important aspects of creating computer educational games.